Pengaruh Social Media Marketing dan Lifestyle terhadap Purchase Decisions melalui Brand Awareness - Chandra; Wendy; Ahmadi; Erna Listiana; Ana Fitriana (PT. PENERBIT TIGA MUTIARA, 2025)
This study aims to comprehensively investigate the influence of Social Media Marketing and Lifestyle on consumer Purchase Decisions, with Brand Awareness serving as a mediating variable that plays a pivotal role in the consumer decision-making process. The research adopts a causal-quantitative design, intended to identify and test the causal relationships among the predetermined variables. Primary data were collected through the distribution of questionnaires to 130 respondents, consisting of customers of CW Coffee in Pontianak City, West Kalimantan. Data analysis was conducted using the Structural Equation Modeling (SEM) technique based on Partial Least Squares (PLS), operated through SmartPLS 4 software, which facilitates simultaneous evaluation of both the measurement model (outer model) and the structural model (inner model). The model estimation results indicate that both Social Media Marketing and Lifestyle exert a positive and statistically significant effect on Brand Awareness, and contribute both directly and indirectly to Purchase Decisions. Furthermore, Brand Awareness is empirically validated as a partial mediator that reinforces the relationship between the independent variables and the dependent variable. The theoretical implications of these findings underscore that enhancing brand exposure through strategic social media engagement and contextually understanding contemporary consumer Lifestyles are critical determinants in shaping strong brand perceptions and driving purchase intention and realization. Consequently, this study offers practical contributions for business practitioners in formulating digital marketing strategies based on the integration of consumer values and the optimization of digital communication channels, thereby enhancing market penetration effectiveness and fostering long-term customer loyalty.